2020
DOI: 10.7554/elife.58019
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and transcriptomic analysis of Anopheles gambiae oenocytes enables the delineation of hydrocarbon biosynthesis

Abstract: The surface of insects is coated in cuticular hydrocarbons (CHCs); variations in the composition of this layer affect a range of traits including adaptation to arid environments and defence against pathogens and toxins. In the African malaria vector, Anopheles gambiae quantitative and qualitative variance in CHC composition have been associated with speciation, ecological habitat and insecticide resistance. Understanding how these modifications arise will inform us of how mosquitoes are responding to c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…Contact pheromones, including cuticular hydrocarbons (CHCs), are widely used by insects during social or sexual communication 17 , 18 . CHCs are waxy molecules derived from fatty acids via a biosynthetic process that involves desaturases, elongases, fatty acid synthases, and cytochrome P450 enzymes 19 , 20 . Biosynthesis occurs in specific cells called oenocytes, from where they are transported to the surface of the cuticle by lipophorin proteins, where they can regulate permeability in addition to playing pheromonal roles 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Contact pheromones, including cuticular hydrocarbons (CHCs), are widely used by insects during social or sexual communication 17 , 18 . CHCs are waxy molecules derived from fatty acids via a biosynthetic process that involves desaturases, elongases, fatty acid synthases, and cytochrome P450 enzymes 19 , 20 . Biosynthesis occurs in specific cells called oenocytes, from where they are transported to the surface of the cuticle by lipophorin proteins, where they can regulate permeability in addition to playing pheromonal roles 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The sugar diet represents an abundant source of carbons that is re ected in the greater proportion of CHCs, as well as the presence of longer CHCs in the sugar-fed mosquitoes. The blood, whether infected or not, caused the total amount and composition of the CHCs to decrease, especially for the very long-chain CHCs, which may indicate a shortage of carbons and an inhibition/limitation of the fatty acid synthases or elongases activity 2 . Previous studies in Drosophila melanogaster reported similar results, where a diet based on yeast or sugar caused the CHC composition to change in opposite directions 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The free aminoacids obtained through diet such as valine, isoleucine and methionine are substrate for the synthesis of propionyl-CoA by the mosquito, which in conjunction with malonyl-CoA, are incorporated to hydrocarbons to form methyl-branched hydrocarbons (reviewed in, 10) 10 . The CHCs are synthesized from acetyl-CoA in an elongation reaction to form a long-chained fatty acyl-CoA in the oenocytes 2 . Then P450 decarbonylase converts them to long-chained hydrocarbons that are transported to the cuticle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite studies showing oenocytes as lipid-processing cells (Gutierrez et al 2007;Martins et al 2011) their physiological role is not limited to this function (Martins and Ramalho-Ortigão 2012). These cells have been shown to participate in organismal homeostasis (Balabanidou et al 2016;Clark and Dahm 1973;Lycett et al 2006;Marriel et al 2016), in the synthesis of some long hydrocarbon chains of sex pheromones (Grigoraki et al 2020;Wicker-Thomas et al 2009) and other cuticular components (Fan et al 2003), and in the initiation of immune response (Martins et al 2011). Oenocytes also play a role in the differentiation of neurons during embryogenesis of D. melanogaster flies through the secretion of semaforin (Sema2a) a peptide that causes axon elongation (Bates and Whitington 2007).…”
Section: Introductionmentioning
confidence: 99%